Toxic Leadership, Teachers’ Job Satisfaction and Organisational Commitment in Lagos State Tertiary Institutions, Nigeria - Nurudeen Olalekan Orunbon; Rasaki Olanrewaju Lawal; Margaret Modupe Isaac-Philips; Rafiyat Iyabo Salaudeen (Journal of Educational Sciences, 2022)
Employee job satisfaction and organisational commitment are directly influenced by leadership styles. Despite the fact that the good elements of leadership have already been explored, the bad sides of leadership must be addressed as well. This study examined the relationship between school toxic leadership, teachers’ job satisfaction and organisational commitment in Lagos State tertiary institutions. Two hypotheses were set to serve as guides for the study. Correlational and descriptive research designs were adopted while the population comprised all lecturers in Lagos State owned tertiary institutions. The sample size was 240 lecturers after stratifying the population into the institutions nomenclature and thereafter selected through purposive sampling technique. Analysis was carried out using inferential statistics of Pearsons Product-Moment Correlation Analysis. Findings indicated that a negative relationship existed between toxic leadership and teachers’ job satisfaction in Lagos State tertiary institutions and also a negative relationship existed between toxic leadership and organisational commitment in Lagos State tertiary institutions. According to the findings of the study, toxic leadership exists in Lagos State higher institutions. The study recommended that before being placed in leadership roles, tertiary institution lecturers should be exposed to leadership development training and opportunities.